1947
DOI: 10.1084/jem.86.4.293
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Pressures Within Cutaneous Lymphatic Capillaries and the Tissues

Abstract: The formation of lymph takes place in the main through the walls of the minute lymphatic capillaries, the larger channels acting chiefly, if not wholly, as conveyors of this fluid to the blood. To learn something about the forces which tend to promote the formation and flow of lymph in the smallest vessels, the lymph pressure existing within cutaneous lymphatic capillaries in the ears of mice has been compared in the present work with the pressure prevailing in the tissue immediately outside them. This has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1961
1961
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Pressure has been measured in the lymphatic vessels and capillaries in humans, sheep, and rabbits 16–18 . The measurement of lymphatic pressure in small mammals is scarce, but an early study measured pressure of lymphatic vessels in mouse ear 19 . However, there is no report of measuring lymphatic pressure in draining lymph nodes of mouse limbs where arthritis occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure has been measured in the lymphatic vessels and capillaries in humans, sheep, and rabbits 16–18 . The measurement of lymphatic pressure in small mammals is scarce, but an early study measured pressure of lymphatic vessels in mouse ear 19 . However, there is no report of measuring lymphatic pressure in draining lymph nodes of mouse limbs where arthritis occurs.…”
Section: Discussionmentioning
confidence: 99%
“…This transfer of the fluid occurs because the hydrostatic pressure is higher in the tissues than in the lymphatics. McMaster [1947] reported a pressure head of 07 cm of H20 in normal conditions in skin interstitial space rising to the order of 6-0 cm of H20 in oedema. The existence of a positive interstitial pressure under normal states has been challenged by Guyton [1963,1965] and independently by Scholander et al [1968].…”
Section: Discussionmentioning
confidence: 97%
“…One is to be able to collect fluid from the tissues, and the other is to move the fluid away from the site of collection and back, generally via the thoracic duct, into the circulating blood stream. Valuable information has been obtained from in vivo observations of lymphatic function in the amphibian tail [Clark, 1912;Clark and Clark, 1920], in the rabbit ear chamber [Clark and Clark, 1932, 1933, 1937, in rat mesentery [Webb, 1933], in the mouse ear [McMaster, 1947;Pullinger and Florey, 1935], in a variety of acute dissected preparations in mammals [Florey, 1927;Pullinger and Florey, 1935;Smith, 1949] and in the membrane of the bat's wing [Webb and Nicoll, 1944]. There has not been any direct extension of in vivo observations such as these so as to correlate observed physiological function with ultrastructural morphology on the identical vessel.…”
mentioning
confidence: 99%
“…However, Chambers and Zweifach (1947) have shown that hyaluronidase disrupts capillary membrane integrity so that the tissue hydrostatic pressures would be abnormally high after treatment with hyaluronidase. In fact, McMaster (1947) showed that hyaluronidase increased edema fluid pressure by approximately 5 mm Hg. Thus, the effects of hyaluronidase on the negative capsular pressure do not necessarily mean that the negative pressure is an artifact.…”
Section: The Chronic Capsular Methodsmentioning
confidence: 99%
“…Calculated from Starling equation P j -1. Isogravimetric P c (Pappenheimer and Soto-Rivera, 1948) 2 Micropuncture P r (Hargens et al, 1978b) B Lymphatic pressure 1 Pressure in initial lymphatics (McMaster, 1947) fluid pressure and total pressure within the interstitial spaces. As McDonald (1968) pointed out, the pressure beneath normal skin exposed to atmospheric pressure must be essentially atmospheric, i.e., zero.…”
Section: Solid Total and Fluid Pressuresmentioning
confidence: 99%